The Rise of Flexing among Muslim Youth on Social Media - Syah, Irfan Padlian; Farhan, Ahmad Alam; Salsabil, Shoopa Alifiah; Rosa, Andi; Muhsin, Masrukhin (FiTUA: Jurnal Studi Islam, 2025)
In recent years, the development of the times, technological advancements, and the rapid flow of information have made social media increasingly popular with various phenomena and trends that have grown into people's habits in the digital era. As long as the trend does not contradict the teachings of the Qur'an, it can be considered reasonable. However, problems arise when the growing trend is not in line with the values of the Qur'an and Hadith. One example is the flexing trend that is rampant by a number of circles, such as celebrities, artists, celebrities, and officials. The focus of this research lies in how flexing is understood in a social context, how to analyze the impact of the flexing phenomenon on social media, as well as examining how Islam views the practice. This study uses a qualitative-descriptive method with a library research approach. The phenomenon of flexing is clearly contrary to the moral teachings brought by the Prophet Muhammad (saw) as stated in the Qur'an and hadith. This behavior is prohibited because it contains various despicable elements that receive a strong threat from Allah SWT. Through the solutions that have been offered in Islam, namely zuhud and tawāḍu' behavior, it is hoped that it can be the main provision in facing the rapid trend and lifestyle that is rampant in the digital era